Electroplating - Sebayang, Darwin; Bin Haji Hasan, Sulaiman (IntechOpen, 2012)
This book emphasizes on new applications of electroplating with consideration for environmental aspect and experimental design. Written by experienced expert from various countries, the authors come from academia and electroplating industrial players. Here, a very detailed explanation to the new application of the electroplating is followed by a solution of the environmental issue caused by the electroplating process and concluded by experimental design for optimization of electro deposition processes. Coverage included: - Preparation NiO catalyst on FeCrAl Subtrate Using Various Technique at Higher Oxidation Process - Electrochemical properties of carbon- supported metal nanoparticle prepared by electroplating methods - Fabrication of InGaN-Based Vertical Light Emitting Diodes Using Electroplating - Integration Of Electrografted Layers for the Metallization of Deep Through Silicon Vias - Biomass adsorbent for removal of toxic metal ions from electroplating industry wastewater - Resistant fungal biodiversity of electroplating effluent and their metal tolerance index - Experimental design and response surface analysis as available tools for statistical modeling and optimization of electrodeposition processes